2012
DOI: 10.5772/56127
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Exposure to Trans Fat in Canada

Abstract: et al.; licensee InTech. Ceci est un article en libre accès distribué sous les termes de la Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), qui permet l'utilisation illimitée, la distribution et la reproduction sur tout support, à condition que le travail original soit correctement cité.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Although trans fatty acids were not the focus of this study, the observation that the RBC contained only a small amount of 9t-16:1 (a characteristic trans fatty acid of dairy fats) and had no trans isomers of oleic and linoleic acids (typical trans fatty acids of partially hydrogenated oils) supports our previous findings which showed that Canadian foods, the current Canadian diet [51,52] and Canadian human milk contained very little trans fatty acids [53]. These low levels of dietary trans fats are the result of the industry's efforts to replace partially hydrogenated oils with liquid vegetable oils in the preparation of prepackaged foods and restaurant fast foods.…”
Section: Discussionsupporting
confidence: 86%
“…Although trans fatty acids were not the focus of this study, the observation that the RBC contained only a small amount of 9t-16:1 (a characteristic trans fatty acid of dairy fats) and had no trans isomers of oleic and linoleic acids (typical trans fatty acids of partially hydrogenated oils) supports our previous findings which showed that Canadian foods, the current Canadian diet [51,52] and Canadian human milk contained very little trans fatty acids [53]. These low levels of dietary trans fats are the result of the industry's efforts to replace partially hydrogenated oils with liquid vegetable oils in the preparation of prepackaged foods and restaurant fast foods.…”
Section: Discussionsupporting
confidence: 86%
“…The 59th session of the WHO Regional Committee for the Eastern Mediterranean (2012) adopted the resolution EM/RC59/R.2, thus endorsing the regional Framework for Action on the commitments of Member States to implement the United Nations Political Declaration on Non-Communicable Diseases [ 1 ]. In its EM/RC59/R.2 resolution, the WHO EMRO urged the Member States to implement the core set of interventions in the regional Framework for Action, with these interventions including the reduction of the population’s salt intake levels and the replacement of trans fat with polyunsaturated fat [ 69 , 70 , 71 ]. Halt diabetes and obesity : WHO EMRO is working closely with governments to achieve the seventh global target of the Global strategy on diet, physical activity and health that aims to halt the rise in diabetes and obesity [ 5 ].…”
Section: Regional Strategies To Reduce Fat (Total Fat Sfas and Tfasmentioning
confidence: 99%
“…In comparison, the success of voluntary trans fat reduction in the Canadian food supply is largely attributable to Health Canada's Trans Fat Monitoring Program, which conducted planned, periodic analysis and public reporting of the trans fat content in foods (Ratnayake et al 2009a(Ratnayake et al , 2009bKrenosky et al 2012). A recent assessment found that 97% of Canadian packaged and restaurant foods fall within the recommended trans fat limits (Arcand et al 2014b).…”
Section: Discussionmentioning
confidence: 99%